Research on the Influence of Work Culture, Commitment, Discipline, on Employee Job Satisfaction Pt. Yamaha Indonesia Motor Manufacturing - Finny Aulia Hidayat; Puspita, Dwi; Maulana, Bagaskoro; Maulana, Andri; Latif, Abdul (Noble Cendekia Indonesia, 2024)
This study aims to analyze the influence of work culture, commitment, and discipline on employee job satisfaction at PT Yamaha Indonesia Motor Manufacturing. The independent variables in this study are work culture, commitment, and discipline, while the dependent variable is employee job satisfaction. The research method used is a quantitative method with a survey approach. The population in this study were all permanent employees of PT Yamaha Indonesia Motor Manufacturing. The sample was determined by simple random sampling technique, so that 100 respondents were obtained. Data collection using a questionnaire, while data analysis using multiple linear regression analysis. The results showed that work culture has a positive and significant effect on employee job satisfaction. Discipline also has a positive and significant effect on employee job satisfaction. Meanwhile, commitment has no significant effect on employee job satisfaction. Simultaneously, work culture, commitment, and discipline have a significant effect on employee job satisfaction. The implication of this research is the need for PT Yamaha Indonesia Motor Manufacturing to continue to strengthen a positive work culture and increase employee commitment in order to increase employee job satisfaction. In addition, the company also needs to pay attention to aspects of employee discipline in order to support increased job satisfaction.